New species and records of Omaliini McLeay, 1825 from Eastern Palaearctic and Oriental regions (Coleoptera: Staphylinidae: Omaliinae) - Shavrin, Alexey V. (Zootaxa, 2022)
New taxonomic and faunistic data for fifteen species of the tribe of Omaliini McLeay, 1825 from the eastern Palaearctic and Oriental regions are provided. Five species are described and illustrated as new: Carcinocephalus cuccodoroi sp.n. (India: Assam), Paraphloeostiba gracillima sp.n. (Thailand: Chiang Mai), P. moluccensis sp.n. (Indonesia: Yamdena Island), P. subuliformis sp.n. (Laos), and Tetradelus sinensis sp.n. (China: Yunnan). The aedeagus, abdominal segments and spermatheca of Acrolocha wahuiense Zhong, Zhao & Li, 2009, and abdominal segments of the female of P. cooteri Shavrin, 2020, previously known only on males, are illustrated. New records are presented: Nipponophloeostiba longilobata Shavrin, 2020 and Paraphloeostiba formosana Shavrin & Smetana, 2016 from India, P. cooteri from Fujian and Guangdong provinces of China, P. gayndahensis (MacLeay, 1873) from India and Nepal, P. opacicollis Steel, 1960 from Malaysia, Phloeonomus (s.str.) pusillus (Gravenhorst, 1806) from Pakistan, and Phloeostiba plana (Paykull, 1792) from China.